Methicillin-resistant Staphylococcus aureus appendicitis - Aditya Safaya; Morgan Stockberger; Karl I. Li; Guiqing Wang; Seunghwan Pee; Gustavo Stringel (Elsevier, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) is commonly isolated from complex intra-abdominal infections. There have been reports of MRSA isolates from various abdominal infections such as diverticulitis, spontaneous bacterial peritonitis and infected peritoneal dialysis catheters. However, there has been no report of MRSA infection related to appendicitis.We present the first case series of MRSA isolated from the abdominal fluid of two patients presenting with appendicitis and managed with laparoscopic appendectomy. Both patients were found to have MRSA isolates from the peritoneal fluid culture.The two patients underwent successful laparoscopic appendectomy and were discharged on appropriate antibiotic coverage for MRSA to complete the course of treatment.Multiple strategies have been involved to manage MRSA infection. Appropriate targeted therapy with source control remains the mainstay of intra-abdominal infections. We present two cases with MRSA isolates from the peritoneal fluid of patients with acute appendicitis. This finding highlights the importance of obtaining intra-operative cultures during appendectomies to guide post-operative antibiotic therapy. Appropriate antimicrobial therapy is the mainstay of treating these infections and preventing the emergence of multi-drug resistant organisms. Keywords: MRSA, MRSA appendicitis, Intra-operative peritoneal cultures